THE AMPHIBIANS AND REPTILES OF RAWA AOPA WATUMOHAI NATIONAL PARK, SOUTHEAST SULAWESI - Mohammad Ali Ridha; Mirza Dikari Kusrini; Ani Mardiastuti; Nancy Karraker (Media Konservasi, 2021)
Rawa Aopa Watumohai National Park (105.194 ha) in Southeast Sulawesi is one of the important conservation areas in Wallacea. This study aimed to measure the diversity of herpetofauna, relative abundance and community similarity in four different habitats. Survey were conducted in January-April 2018 using Visual Encounter Survey (VES) based on time and transects in savanna, riparian, lowland forest, and mangrove. Forty-two species from 17 families were found consisting of 10 species of amphibians and 32 species of reptiles, in which 9 species are endemic i.e. Papurana celebensis and Draco beccarii. The highest diversity (H’) and evenness (E) indexes was found in lowland forest (H’ = 2.497, E = 0.555). The most abundant amphibian was Limnonectes modestus with 85 individuals (23.8%), while the most abundant reptile was Crocodylus porosus with 24 individuals (6.7%). The similarity of communities between the four habitats was low (<0.5), indicating that most species are specialists on particular habitats. Although diversity was relatively low in Rawa Aopa Watumohai National Park, high endemism warrants ongoing efforts to conserve amphibians and reptiles in this national park. Key words: herpetofauna diversity, Indonesia, lowland forest, national park, Sulawesi